The Main Ideas of Cosmology at School. (21st May 2015) - Novotny, Jan; Svobodova, Jindriska
Abstract: The aim of this research study was to investigate students' ideas and main difficulties with understanding modern cosmology science and to design based on results obtained a new cosmology course. We tried to identify factors, which might limit students' skills and knowledge about universe. The participants were students – mostly pre-service teachers at the Science Education program in an Faculty of Education. A combination of qualitative and quantitative research approaches were used in the study. The data were primarily sourced from a standard questionnaire instrument. In addition, the interviews were conducted to determine student's views of discussed course topics.